We can simplify question to:

(n-1)(n+3-n+2) = m(n-1)

(n-1)*5 = m*(n-1)

m*(n-1) - 5*(n-1) = 0

(m-5)*(n-1) = 0 ............. (A)

Now, stmt 1: |m| = 5, i.e. m=5, or m = -5

If m = 5, then (A) becomes 0*(n-1) = 0, so n can be any value.

If m = -5, then (A) becomes -10*(n-1) = 0 or n = 1

Hence insufficient. Eliminate A,D

Now, stmt 2: m = 5, similar to above, (A) becomes 0*(n-1) = 0, so n can be any value.

Hence Insufficient. Eliminate B

Now, Combined, we get the condition, m = 5, again (A) becomes 0*(n-1) = 0, so n can be any value.

Hence insufficient. Eliminate C.

So as per my analysis, answer should be

Option E
_________________

If you found this relevant and useful, please Smash that Kudos button!